Quality disclosure in reporting sustainable communication in public listed companies, Malaysia - Abdul Aziz, Nor Shahira (2018)
Although most companies in Malaysia are starting to communicate its sustainability practices, there is considerable doubt on the quality of indicators disclosed in the Sustainability Reporting. Whether the company communicates it accurately and completely portray its impacts. Disclosing low-quality information to stakeholders will hinder effective communication in company sustainable development. Previous studies have found that Sustainability Reporting in Malaysia is still generally low and has developed at a slower pace compared to other countries. The purpose of this research is to investigate the quality of indicators disclosed in Sustainability Reporting among companies from different industries in Malaysia. The quality of three main indicators under the sustainability concept which are economic, environmental and social disclosures reported by companies are studied. This research investigates the quality of economic indicators, environmental indicators and social indicators disclosed in Sustainability Reports based on the industries which the companies belong. Sustainability Reports of Top 30 public listed companies in Malaysia are studied. To achieve the said purposes, observations on companies Sustainability Report are conducted using a content analysis research method. This method allows the researcher to observe and evaluate Sustainability Reports of the companies using the Global Reporting Initiative (GRI) framework as a guideline. Data analysis by univariate analysis and descriptive analysis such as frequencies are reported. The result shows that the quality of sustainable indicators disclosed by Top 30 Public listed companies in Malaysia is relatively low. Among the three performance indicators, the economic dimension has the highest quality indicators disclosed by company followed by environmental dimension and lastly social dimension. This study revealed that companies focus more on economic dimension when reporting Sustainability as a group of stakeholders such as investor and shareholders that usually interested in this topic hold more power, legitimacy, and urgency in the continuity of company business. The quality of economic indicators disclosed in the Sustainability Report of companies among different industries shows that the telecommunication industry disclosed the most quality indicators compared to others. Telecommunication industry also disclosed better social indicators than other industry. It shows that different industry has its own focus when communicating sustainability in line with their communication objective. Meanwhile, in the environmental aspect, manufacturing, and real estate industry disclosed the most quality indicators. As companies operate in a high-risk industry, they tend to disclose more information to communicate their practices in order to gain confidence and stay legitimate in front of society. This study further concludes that even though all of the companies disclosed its sustainability indicators, the quality is far from perfect. Most of the indicators disclosed are in favor of the company and mostly communicate on the achievement and contribution of the companies. It can be seen that the majority of the companies listed on Bursa Malaysia are not yet ready to communicate a quality sustainable communication with their stakeholders although it is very important in managing stakeholders’ expectation. This current study contributes to the body of knowledge in the field of corporate sustainability by integrating sustainable communication and stakeholders management models in the Malaysian setting. This study emphasized that company practices sustainable performance to manage stakeholders’ relation and obtain legitimacy. The findings provide input to regulatory bodies especially the government on the quality of indicators disclose on the Sustainability Reports by listed companies in Malaysia.